Risk factors for Coronavirus disease-associated mucormycosis. Issue 3 (March 2022) - Arora, Umang; Priyadarshi, Megha; Katiyar, Varidh; Soneja, Manish; Garg, Prerna; Gupta, Ishan; Bharadiya, Vishwesh; Berry, Parul; Ghosh, Tamoghna; Patel, Lajjaben; Sarda, Radhika; Garg, Shreya; et al.
Highlights: A case-control study was performed to assess factors associated with occurrence of Coronavirus-disease associated mucormycosis, an invasive fungal infection that led to a syndemic during the second wave of COVID-19 in India. Diabetics and patients receiving steroid therapy are at increased risk of CAM. The role of mask type and hygiene, repeated nasopharyngeal swab testing and zinc supplementation as modifiable factors to prevent CAM merits further study. Abstract: Background: The epidemiology of the Coronavirus-disease associated mucormycosis (CAM) syndemic is poorly elucidated. We aimed to identify risk factors that may explain the burden of cases and help develop preventive strategies. Methods: We performed a case-control study comparing cases diagnosed with CAM and taking controls as recovered COVID 19 patients who did not develop mucormycosis. Information on comorbidities, glycemic control, and practices related to COVID-19 prevention and treatment was recorded. Multivariate regression analysis was used to identify independent predictors. Results: A total of 352 patients (152 cases and 200 controls) diagnosed with COVID-19 during April-May 2021 were included. In the CAM group, symptoms of mucormycosis began a mean of 18.9 (SD 9.1) days after onset of COVID-19, and predominantly rhino-sinus and orbital involvement was present. All, but one, CAM cases had conventional risk factors of diabetes and steroid use. On multivariable regression, increased odds of CAM were associated with the presence of diabetes (adjusted OR 3.5, 95% CI 1.1–11), use of systemic steroids (aOR 7.7, 95% CI 2.4–24.7), prolonged use of cloth and surgical masks (vs. no mask, aOR 6.9, 95%CI 1.5–33.1), and repeated nasopharyngeal swab testing during the COVID-19 illness (aOR 1.6, 95% CI 1.2–2.2). Zinc therapy was found to be protective (aOR 0.05, 95%CI 0.01–0.19). Notably, the requirement of oxygen supplementation or hospitalization did not affect the risk of CAM. Conclusion: Judicious use of steroids and stringent glycemic control are vital to preventing mucormycosis. Use of clean masks, preference for N95 masks if available, and minimizing swab testing after the diagnosis of COVID-19 may further reduce the incidence of CAM.